Laser cladding of Al-50Si alloy - Muhammad Wa'ie Jumat (Nanyang Technological University, 2022)
The microstructures of the a layer of clad Al-50Si alloy on a Al7075 substrate were studied over varying laser powers. The observation of the microstructures were examined using a Stereo and Optical microscope and the Agilent Nano Indenter G200 equipment was used to determine the Hardness and Modulus of the alloy. The microstructures of the cladded region was categorized to three regions of the substrate – i) the Primary Silicon region ii) the Eutectic Silicon region and iii) the Substrate interface region was investigated, and this region is made up of Si primary particles, Al dendrites and eutectic Al-Si at these regions. The sizes of Si particles reduce as laser was applied towards a single direction. After solidification at a low laser power wattage, was observed to contain porosities at the mid-section of the substrate while cracks are found on the substrate interface when a higher laser power was utilized. The microstructure of the Si particles generally reduces at a higher laser power. Furthermore, it is discovered that at a higher laser power, the Hardness and Modulus values reduces but insignificantly.